Innovative Methods To Increase Physical Activity Among School-Age Children In Uzbekistan: Technological And Pedagogical Innovations - Mamadiyorov Norbek Kuvandikovich (Zien Journals, 2025)
Physical inactivity among youth is a growing concern in Uzbekistan, mirroring global trends. This article examines innovative approaches to increase physical activity in children aged 6–17, focusing on technological tools (digital apps, wearables, exergames) and pedagogical strategies (curriculum reforms, active schools, teacher training). By integrating evidence from international research and local initiatives, the study highlights how combining digital engagement with educational reforms can enhance youth physical activity and improve health outcomes.
Keywords: Physical activity; School-age children; Uzbekistan